Penyuluhan Kesehatan Menggunakan Media Flipchart Meningkatkan Stigma Positif Masyarakat tentang ODHA - G. Nur Widya Putra; Putu Agus Ariana; Ni Luh Gede Melda Rosita (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of health education on HIV/AIDS using flipchart media on community stigma in Munduk Village. The design of this research is pre-experimental with a one-group pre-post-test design. The results showed that the stigma of respondents before being given health education about HIV/AIDS using flipchart media, on average, had a high negative stigma about HIV/AIDS (81.1 %). After being given health counseling, most respondents (70.3%) have a low negative stigma about HIV/AIDS. The results of the bivariate analysis showed a p-value of 0.005. In conclusion, health education using flipchart media effectively increases positive stigma about PLWHA in the community in Munduk Village, Buleleng Regency. Keywords: PLWHA, Health Counseling, Stigma